The Effects Of Perception On Learning Styles And Creativity Towards Students’ Speaking Skill Survey At State Senior High Schools In Cirebon City, West Java - Siti Komala; Lilis Suharti (KOMVERSAL, 2023)
ABSTRACT This research is a kind of and aims to find out analyzes empirically the effects of perception on learning styles and creativity on students’ speaking skill. The population of the research is twelfth graders from state senior high schools in Cirebon. The sample was taken from three state senior high schools. The research has 3 variables which are divided into 2 independent variables (Perception on learning styles and creativity) and 1 dependent variable (students’ speaking skill). The collection of the data was taken from two kinds of questionnaire for independent variables and teachers’ file on speaking scores for dependent variable. The gained data was analyzed by using correlation technique and double linear regression. The research findings were: 1) There are significant effects of perception on learning styles and creativity jointly on students’ speaking skill at state senior high schools in Cirebon city. It was proved by the score of Sig 0.000 < 0.05 and Fcount = 23.510 2) There was a significant effect of perception on learning styles on students’ speaking skill at state senior high schools in Cirebon city. It was proved by Sig 0.007 < 0.05 and tcount = 2.759 3) There was a significant effect of creativity on students’ speaking skill at state senior high schools in Cirebon city. It was proved by Sig 0.000 < 0.05 and tcount = 4.745 Key words: Learning Style, Creativity, and Speaking Skill ABSTRAK Penelitian ini merupakan salah satu jenis dan bertujuan untuk mengetahui analisis secara empiris pengaruh persepsi terhadap gaya belajar dan kreativitas terhadap keterampilan berbicara siswa. Populasi penelitian ini adalah siswa kelas XII SMA Negeri di Cirebon. Sampel diambil dari tiga sekolah menengah atas negeri. Penelitian ini memiliki 3 variabel yang terbagi menjadi 2 variabel bebas (Persepsi terhadap gaya belajar dan kreativitas) dan 1 variabel terikat (keterampilan berbicara siswa). Pengumpulan data diambil dari dua jenis angket untuk variabel bebas dan arsip guru tentang nilai berbicara untuk variabel terikat. Data yang diperoleh dianalisis dengan menggunakan teknik korelasi dan regresi linier berganda. Temuan penelitian ini adalah: 1) Terdapat pengaruh signifikan persepsi gaya belajar dan kreativitas secara bersama-sama terhadap keterampilan berbicara siswa SMA Negeri di kota Cirebon. Dibuktikan dengan nilai Sig 0,000 < 0,05 dan Fhitung = 23,510 2) Terdapat pengaruh yang signifikan persepsi gaya belajar terhadap keterampilan berbicara siswa SMA Negeri di kota Cirebon. Dibuktikan dengan Sig 0,007 < 0,05 dan thitung = 2,759 3) Terdapat pengaruh yang signifikan kreativitas terhadap keterampilan berbicara siswa SMA Negeri di kota Cirebon. Dibuktikan dengan Sig 0,000 < 0,05 dan thitung = 4,745 Kata Kunci: Gaya Belajar, Kreatifitas, dan Keterampilan berbicara